2,2′,7,7′-Tetrabromo-9,9′-spirobifluorene toluene hemisolvate - Guo, Ailing (International Union of Crystallography, 2009)
There are two independent molecules and one toluene solvent molecule in the asymmetric unit of the title compound, C(25)H(12)Br(4)·0.5C(7)H(8). The dihedral angles between the fluorene ring systems are 85.30 (6) and 84.95 (6)° in the two molecules. The disortions in angles from the ideal sp (3)-hybridization geometry around the tetrahedral C atoms are due to the strain imposed by the central five-membered ring and steric effects.